PERILAKU AFEKTIIF PERILAKU AFEKTIIF: PERILAKU AFEKTIIF - Alun Matiti; Frezy Paputungan (LPPM UNiversitas Bina Mandiri Gorontalo, 2022)
This article discusses affective behavior, which is itself a natural thing and an integral part of human experience. The emotions and feelings we feel play an important role in shaping our response to the environment and also affect our quality of life. This article is presented using qualitative methods. Affective behavior is an important aspect of human life that involves a person's emotional reactions, feelings, and moods. The term